Harnessing rural households’ intentions to adopt ethnobotanical knowledge - Monika, A; Nirmala Devi, M; Karthikeyan, C; Premavathi, R; Selvanayaki, S; Gangai Selvi, R (Plant Science Today, 2025)
Ethnobotanical practices, rooted in indigenous knowledge, offer sustainable solutions for health, nutrition and agriculture, yet their adoption remains understudied, due to socio-economic or institutional constraints. This research examines factors influencing farmers’ intention to adopt ethnobotanical practices in Coimbatore district, Tamil Nadu. It aims to identify the key drivers and barriers. Using a quantitative method, data were collected through interviews with 540 respondents across 12 blocks and analyzed using Structural Equation Modeling (SEM). Results indicate that Perceived Benefits (PB), Perceived Ease of Use (PEOU), Social Influence (SI) and Access to Resources (AR) positively influence adoption, while Institutional Support (IS) showed a weak negative correlation, suggesting inadequate alignment with local needs. The study highlights the potential of Farmer Producer Organizations (FPOs) as catalysts for integrating traditional knowledge with modern agricultural systems through improved resource access and collective marketing. Key findings underscore the importance of community-centric approaches in promoting ethnobotanical practices, emphasizing the need for policy reforms to enhance institutional responsiveness. The study concludes that empowering FPOs to bridge indigenous and scientific knowledge systems can significantly improve rural livelihoods, health resilience and agricultural sustainability. Recommendations include strengthening local capacity-building initiatives, refining extension services to better incorporate traditional wisdom and fostering participatory models of knowledge exchange. These insights provide actionable pathways for policymakers and development practitioners to leverage ethnobotanical knowledge for sustainable rural transformation.